Perencanaan Sheet Pile dengan menggunakan Program Plaxis (Studi Kasus : Jalan Padang Tambak – Liwa KM.227+400) - Agatha, Muhammad Naufal; Adha, Idharmahadi; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Soil landslide is one of the most common in the field of Geotechnical due to increased shear stress of a soil mass or decrease in shear strength of the soil mass. In other words, the shear strength of the soil mass is not able to bear the burden of work going on. Disruption to the stability of the slope can be caused by various human activities and natural conditions. Unstable slopes is dangerous to the surrounding environment, therefore slope stability analysis is needed. In this case the condition of Padang Tambak – Liwa street KM.227+400 Lampung Barat experience landslide up the road. The purpose of this study is to evaluate the value of the safety factor and to plan the dimension and stability of sheet pile to the landslide on Padang Tambak – Liwa street KM.227+400 using the Plaxis v.8.2 of computer program. The result of this study obtained the value of safety factor at the initial condition of 0,7106, with displacement of 12,71 x 103 m. The handling of reinforcement slopes of sheet pile profiles of type OT26 U profile which is placed at 2,5 meters from the middle of the highway with a size of 12 meters and then replace the soil layer 1 on the outside of the sheet pile into a slope-like slope soil and reduce the slope to 32° level obtained factor value safety at 1,1532, with displacement of 145,88 x 10-3 m. Handling by reinforcing sheet pile profiles of type OT26 U profile in this condition was considered safe because it met the requirement of safety factor value and had a small displacement value.Keywords: slope stability, safety factor, plaxis, sheet pile, displacement.